(untitled) (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2020)
A MCU-based fish feeder with SMS notification is a microcontroller device that is run by Arduino Uno. The fish feeder was designed ergonomically and is a user-friendly device that can help fish farmers with its versatile and functional features. A MCU-based fish feeder with SMS notification has a scheduling system to help the fish farmers feed the fish at a specific time. The device is also equipped with an ultrasonic sensor to notify the user if the fish pellets are at a critical point and would send data to the GSM module to notify the user via SMS message to restock fish pellets. The device power source was controlled by a sealed rechargeable battery, and the device is electrically supplied by a solar panel. Lastly, it can distribute 1 kg food pellets in 43 s. The mechanism of the device was prototyped by an auger together with a stepper down motor for dispensing feeds from the hopper storage to the centrifugal blower that would throw the pellets to the fishpond for approximately 23–25 ft. long-range and can occupy 60 sq areas of the fishpond.Keywords: